The Tate Gallery 1984-86 : Illustrated Biennial Report. - Tate Gallery, London (Londen : Tate Gallery, 1986)
Matisse, Henri ; De Chirico, Giorgio ; Schwitters, Kurt ; Picabia, Francis ; Hillier, Tristram ; Appel, Karel ; Jorn, Asger ; Rothko, Mark ; Beuys, Joseph ; Kiefer, Anselm ; Dimitrijevic, Braco ; etc.
Contents: Historic British Collection Acquisitions, Modern Collection Acquisitions, Print Collection ; Exhibitions ; Education ; Publications ; ...
Engels
boek